Evaluation of motivational, challenges and critical success factors in managing halal-certified restaurants in the Klang Valley, Malaysia - Razali, Nor Ellyna (2019)
The growing awareness on Halal concept among consumers has increased the demand for Halal products and services. Hence, it is pivotal that these Halal products and services are readily available, especially for the Muslims. In Malaysia, the availability of Halal products, excellent hospitality, various services, and pristine natural environment have placed it as one of the top Islamic tourism destinations especially among Middle Eastern tourists. However, the number of Halal-certified food premises remains scarce despite the recent development of the foodservice industry. Additionally, the critical success factors to the implementation of Halal certification system in the foodservice industry, especially in restaurants, remain underexplored. Thus, this study aimed to identify motivational, challenges, and critical success factors in managing Halal certified restaurants in Malaysia. This study conducted a semi-structured interview approach, which involved 21 respondents including Halal executives, managers or supervisors, owners and JAKIM officers. Using ATLAS.ti (version 7), this study analysed the coded interview transcripts to identify any emerging themes and pattern with respect to the objectives of this study. This study further revealed (1) customers‘ expectations and satisfaction, (2) restaurant image and reputation, (3) positive business performance, (4) top management support, (5) product quality and safety, and (6) support from authorities as motivational factors to the implementation of Halal certification in restaurants. Besides, this study also identified several challenges to the implementation of Halal certification in restaurants, namely (1) employee issues, (2) supplier and logistic, (3) complicated requirement and process (4) consultant limitation, and (5) restaurant attributes. Furthermore, the identified critical success factors were (1) top management commitment, (2) employee attributes, (3) company attribute, (4) supplier commitment, (5) managerial role, (6) teamwork, and (7) restaurant internal operation. Conclusively, this study obtained in-depth insights on these key aspects that influence the implementation of Halal certification in restaurants within the Malaysian context.